Development E-Student Worksheet Using Guided Inquiry Learning Model - Dilla Maidaliza; Ramalis Hakim; Zuwirna Zuwirna; Abna Hidayati (Jurnal Penelitian Pendidikan IPA, 2024)
Based on observations of science subject teachers, several obstacles were encountered in learning activities, the teaching materials used by the school did not support the needs of the student learning process which resulted in low student learning outcomes. The purpose of this study was to produce teaching materials in the form of E-Student Worksheet in science subjects for grade VII of SMP/MTs that were valid, practical, and effective. This type of research is Research and Development with the ADDIE development model. The results of the study obtained validation in the media aspect with a percentage of 89.6% in the material aspect with a percentage of 84.4% and the language aspect with a percentage of 86.9%, so E- Student Worksheet using a guided inquiry learning model was stated as very valid. Practicality assessment was obtained through a questionnaire assessment by teachers with a percentage of 97.14 % and by students with a percentage of 91.43%, so E- Student Worksheet using a guided inquiry learning model was stated as very practical. The effectiveness test was conducted at SMP Negeri 23 Padang through pretest and posttest, obtaining a gain score of 0.8 classes with a very high category. The average learning outcomes of students after using E- Student Worksheet using guided inquiry learning model in class VII.3 is 93% with a very effective category. Based on the data above, it can be concluded that E- Student Worksheet using guided inquiry learning model in science subjects in junior high schools/Islamic junior high schools is valid. Practical, and effective to use in learning activities.